Current status of the Palm collection (Arecaceae) of the Venezuelan National Herbarium (VEN) - Espinoza Flores, Yaroslavi (2008)
The National Herbarium of Venezuela (VEN) has the largest collection of botanical specimens in the country,thus being the main source of reference for the flora of Venezuela. It also hosts a large number of specimensfrom other countries in the Neotropical region. The VEN contains approximately 400 000 specimens currentlyregistered in the herbarium’s database, of which 2192 form the palm (Arecaceae) collection that encompasses35 genera (including 5 foreign genera) and 127 specific and infraspecific taxa. The genera with the largestnumber of specimens are Geonoma (498) and Bactris (360), followed by Euterpe (158). The species Geonomadeversa (Poit.) Kunth contains the largest number of specimens in the collection (110). The herbarium hosts typematerial of 12 Arecaceae taxa: 4 holotypes, 1 lectotype, 5 isotypes and 2 isoneotypes. Most of the specimensat the VEN have been identified by specialists such as A. Henderson, F. Kahn, F. Stauffer and J. Wessels-Boer. A list of species found in the herbarium is presented herein. Review of specimen data at the VEN showthat palms have been collected mainly in the following states of Venezuela: Amazonas, Bolivar, Zulia, DeltaAmacuro, Aragua, Apure, and Distrito Capital. The main contribution to the collection of palms to the VEN isthe collections made by J. A. Steyermark and F. Stauffer.